2020
DOI: 10.4103/ajns.ajns_255_19
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic epidural lipomatosis associated with degenerative discopathy: Grand round presentation of unusual lumbar canal stenosis resolved by weight loss

Abstract: Here, we report a case of idiopathic epidural lipomatosis presented with a clinical picture of lumbar canal stenosis with neurogenic claudication which resolved completely only by weight loss. A 53-year-old obese male with a body mass index of 36 without significant past medical history presented to the outpatient clinic with neurogenic claudication and bilateral sciatic radiculopathy. Initially, magnetic resonance imaging (MRI) showed epidural lipomatosis at the level of L5 vertebral body and L5–S1 interverte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Weight reduction has been identified to have a positive impact in the treatment of obese patients with SEL. [ 11 17 18 19 20 21 22 23 24 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Weight reduction has been identified to have a positive impact in the treatment of obese patients with SEL. [ 11 17 18 19 20 21 22 23 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of SEL ranges from conservative management [ 11 17 18 19 20 21 22 23 24 25 26 ] to surgical excision. [ 5 21 25 26 27 ] There are many cases reported the resolution of SLE on losing weight either by a structured weight loss program and/or by the help of bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 In some cases, weight loss alone was sufficient to alleviate the clinical symptoms and reduce the volume of epidural adipose tissue. 12,13 Some scholars have suggested that for every percentage point increase in body weight, the likelihood of suffering from SEL increases by 13%. 14 Up to now, although many literature has shown that obesity has a clear correlation with SEL, most of them are isolated case reports and small sample case series.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, weight loss alone was su cient to alleviate the clinical symptoms and reduce the volume of epidural adipose tissue [12,13]. Some scholars have suggested that for every percentage point increase in body weight, the likelihood of suffering from SEL increases by 13% [14].…”
Section: Introductionmentioning
confidence: 99%